Frankenstein - Shelley, Mary; Mohammed, Wahed ([Cairo] bayt alkotob publishing, 2025)
When the scientist Victor Frankenstein attempts to create life in his laboratory, he sets in motion tragic forces beyond his control and faces losing everything he loves. No reader in the grip of Mary Shelley$1 (Bs novel, with its mythic-minded hero and its highly sympathetic monster who reads Goethe and longs to be at peace with himself, can fail to notice how much more excellent the original is than all the countless adaptations, imitations, and homages which have followed in its ample wake. In her first novel, written at the instigation of Lord Byron and published in 1818 (and revised in 1831), the teenaged Shelley managed to produce English Romanticism$1 (Bs finest prose fiction. This edition reproduces her original 1818 texts
Keywords: English fiction